Implementation of Provisions on the Rights of Women Nurses Working in Hospitals Based on Human Rights Review - Aprilia Ninda Giasma; Edward Kurnia; Yovita Indrayati (SOEPRA, 2021)
Abstract: One of the health workers is nurses who have the rights as workers and as nurses. The rights that must be fulfilled as nurses and workers are prohibition against labour, protection of female workers at night, menstruation leave, maternity and maternity leave, miscarriage leave and breastfeeding rights, but the implementation has not been carried out optimally.This research is a sociological juridical study with qualitative descriptive research specifications. The study was conducted at the emergency department and hospital inpatient installations. The method of data collection is done by observation and interviews and literature studies to obtain the data needed.The results of the research in the two hospitals showed that the rights of female nurses as workers were contained in company regulations and employment agreements, whereas as a profession there were nurses by-laws and clinical privileges. The regulation of women's nurses' rights is contained in the Labor, Health and Nursing laws. In the implementation of these rights, namely the right of maternity leave and childbirth, the provision of wages during leave and protection of female nurses who work at night and work facilities according to standards have not been carried out optimally. The work agreement does not fulfil one of the legal requirements of the agreement, namely the halal cause and for the company regulation applies the superior lex principle derogate lege inferiori. Factors that influence the implementation of provisions in the form of inhibiting and supporting factors.Keywords: Implementation, Nurse Rights, Women, Human Rights Abstrak: Tenaga kesehatan salah satunya yaitu perawat memiliki hak sebagai pekerja dan sebagai perawat. Hak yang harus dipenuhi sebagai perawat dan pekerja yaitu larangan phk, perlindungan pekerja perempuan pada malam hari, cuti haid, cuti hamil dan melahirkan, cuti keguguran dan hak menyusui, namun dalam pelaksanaannya belum terlaksana secara optimal.Penelitian ini merupakan penelitian yuridis sosiologis dengan spesifikasi penelitian deskriptif kualitatif. Penelitian dilakukan di instalasi gawat darurat dan instalasi rawat inap rumah sakit. Metode pengumpulan data dilakukan dengan observasi dan wawancara serta studi kepustakaan untuk memperoleh data yang dibutuhkan.Hasil penelitian di kedua rumah sakit didapatkan hasil bahwa hak – hak perawat perempuan sebagai pekerja terdapat di dalam peraturan perusahaan dan perjanjian kerja, sedangkan sebagai profesi terdapat di nurse by laws dan clinical privilage. Pengaturan hak perawat perempuan terdapat pada undang – undang tentang Ketenagakerjaan, Tenaga Kesehatan serta Keperawatan. Dalam implementasi hak – hak tersebut yaitu hak cuti hamil dan melahirkan, pemberian upah selama cuti dan perlindungan terhadap perawat perempuan yang bekerja pada malam hari serta fasilitas kerja sesuai standar belum terlaksana secara optimal. Pada perjanjian kerja tidak memenuhi salah satu syarat sahnya perjanjian yaitu kausa yang halal serta untuk peraturan perusahaan berlaku asas lex superior derogat lege inferiori. Faktor – faktor yang mempengaruhi implementasi ketentuan berupa faktor penghambat dan pendukung.Kata kunci: Hak Perawat, Perempuan, Hak Asasi Manusia